Circulating levels and prognostic value of soluble ST2 in heart failure are less influenced by age than N‐terminal pro‐B‐type natriuretic peptide and high‐sensitivity troponin T. (9th January 2020) - Aimo, Alberto; Januzzi, James L.; Vergaro, Giuseppe; Richards, A. Mark; Lam, Carolyn S.P.; Latini, Roberto; Anand, Inder S.; Cohn, Jay N.; Ueland, Thor; Gullestad, Lars; Aukrust, Pål; Brunner‐La Rocca, Hans‐Peter; et al.
Abstract: Aims: N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP), high‐sensitivity troponin T (hs‐TnT) and soluble suppression of tumorigenesis‐2 (sST2) predict outcome in chronic heart failure (HF). We assessed the influence of age on circulating levels and prognostic significance of these biomarkers. Methods and results: Individual data from 5301 patients with chronic HF and NT‐proBNP, hs‐TnT, and sST2 data were evaluated. Patients were stratified according to age: <60 years ( n = 1332, 25%), 60–69 years ( n = 1628, 31%), 70–79 years ( n = 1662, 31%), and ≥ 80 years ( n = 679, 13%). Patients (median age 66 years, 75% men, median left ventricular ejection fraction 28%, 64% with ischaemic HF) had median NT‐proBNP 1564 ng/L, hs‐TnT 21 ng/L, and sST2 29 ng/mL. Age independently predicted NT‐proBNP and hs‐TnT, but not sST2. The best NT‐proBNP and hs‐TnT cut‐offs for 1‐year and 5‐year all‐cause and cardiovascular mortality and 1‐ to 12‐month HF hospitalization increased with age, while the best sST2 cut‐offs did not. When stratifying patients according to age‐ and outcome‐specific cut‐offs, this stratification yielded independent prognostic significance over NT‐proBNP levels only, or the composite of NT‐proBNP and hs‐TnT, and improved risk prediction for most endpoints. Finally, absolute NT‐proBNP, hs‐TnT, and sST2 levels predicted outcomes independent of age, sex, left ventricular ejection fraction category, ethnic group, and other variables. Conclusions: Soluble ST2 is less influenced by age than NT‐proBNP or hs‐TnT; all these biomarkers predict outcome regardless of age. The use of age‐ and outcome‐specific cut‐offs of NT‐proBNP, hs‐TnT and sST2 allows more accurate risk stratification than NT‐proBNP alone or the combination of NT‐proBNP and hs‐TnT.